‘XYZ’ application as a tool for teaching and learning in institutions of higher learning: an exploratory study - Saroja Dhanapal,; Nadhratul Wardah Salman,; Gopinathan K. Raman Kutty,; Khalid M.S. Ansari,; Sardar Ali Shah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Teaching and learning in institutions of higher learning has undergone transformation as a result of rapid development in the field of communication and technologies. The emergence of social networking sites has paved the way for the enhancement of teaching and learning approaches. The focus of this study is on ‘XYZ’ application (the actual name is not disclosed due to confidentiality) that was recently launched in Malaysia. Using a mixed research method, the study investigated the perceptions of undergraduate students in a public university to identify the viability of this application in comparison with other applications and to analyze its effectiveness as a tool for teaching and learning. The findings indicate the application has good features that enhance the effectiveness of the teaching and learning process. However, there is concern about the limited compatibility of this application. The paper ends with recommendations on how the application can be improved.